Identification of Flood Distribution Using Sentinel-1 Satellite Images (Case Study: Gresik Regency) - Siti Zainab; Novie Handajani; Hendrata Wibisana (Future Science, 2021)
Population growth is highly correlated with development activities. Development activities bring changes in land use from one period to the next, bringing relatively high changes, especially changes in land use. Changes in land use that occurs will be a potential for floods, landslides, and prolonged drought if not controlled. It is necessary to do a mapping caused by the impact of the flood disaster, which will later be used as a database which is a regional administration need for land cover information as well as consideration for making a policy for the benefit of the surrounding community. Regional administration needs for land cover information will support planning in an area. Remote sensing is a medium that can monitor the dynamics of land-use change quickly and at a relatively low cost. And by using Sentinel-1 satellite imagery data with the GEE Platform (google earth engine). GEE (google earth engine) is a cloud-based computing platform for performing geospatial analysis, with petabytes of data for scientific analysis and visualization of geospatial data on a global scale. This study aims to identify the distribution of flood areas affected by floods in the Gresik Regency. The results of the study show that the estimated most affected by flooding is the estimated population affected by 6,800,071 Ha. Meanwhile, the next affected area is the Estimated Urban Land of 666,033 Ha. The last estimate affected by the smallest flood is 158,848 hectares of agricultural land. The districts affected by the flood include Cerme, Morowudi, Betatu, Benjeng, Balung Panggang, Gresik Regency.